An overlooked complication after laparoscopic surgery: Trcur site hernias - Sezai YILMAZ; Vedat KIRIMOĞLU; Mehmet ÇAĞLIKÜLEKÇİ and Cüneyt KAYAALP and Fuat ATALAY and Musa AKOĞLU (Turkish Journal of Gastroenterology, 2019)
-